THE CORRELATION BETWEEN THE SECOND YEAR STUDENTS’ CRITICAL THINKING DISPOSITION AND THEIR ABILITY IN WRITING ANALYTICAL EXPOSITION TEXTS AT MAN 1 PEKANBARU - M. Fadhil muzakki; Syofia Delfi; M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed at discovering the correlation between the second year students’ critical thinking disposition and their ability in writing analytical exposition texts at MAN 1 Pekanbaru. The problem needs to be addressed in this research is : is there any significant correlation between MAN 1 Pekanbaru second year students’ critical thinking disposition and their ability in writing analytical exposition texts The research data were collected in April 2017. The population of this research was 301 second year students of MAN 1 Pekanbaru. The cluster random sampling technique was applied to determine the sample. The sample of this research is class 31 students of XI MIA 3. The data were collected by using two kinds of instruments in the form of a questionnaire and a writing test which are assessed by using Product Moment’s formula that are analyzed by using SPSS 16.0 Statistic Program. Based on the data analysis, it shows that there is a significant and positive correlation between MAN 1 Pekanbaru second year students’ critical thinking disposition and their ability in writing analytical exposition texts. The correlation is categorized as moderate level. This study suggests the teacher to promote critical thinking in English classrooms. The implication of the finding is that the students should increase their disposition towards critical thinking to improve their writing.Keywords: Correlation, Critical Thinking Disposition, Writing, Analytical Exposition